Green Entrepreneurship in Developing Countries: A Systematic Review of the driving factors and challenges in realizing sustainable business - Mohammad Kartika; Gani Ramdani; Sudarmiatin; Trisetia Wijijayanti (International Humanity Advance, Business & Sciences, 2026)
The aim of this study was to analyze the growth of green entrepreneurship, also known as green entrepreneurship, in developing countries, with particular emphasis on the components that affect business sustainability. Green entrepreneurship orientation and green innovation are critical to improving the economic, social, and environmental performance of businesses, according to research conducted on fourteen Scopus indexed scientific articles from 2021-2025. However, green practices still face structural challenges such as limited capital, access to green technologies, and limited policy support. It is evident that institutional elements, public policies, and local social and cultural principles play a significant role in strengthening the green entrepreneurship ecosystem. To accelerate the transformation towards a sustainable economy in developing countries, this study confirms that governments, businesses, and communities must work together in various sectors.